Future, change and choices - Nel, Verna (Department of Urban and Regional Planning, University of the Free State, 2010)
Abstract not available
Robinson, P. (2009). Future, Change and Choices - Strategic planning methods for built environment professionals. Westville: Osborne Porter Literary Services. ISBN 978-0-9814276-6-9
Keywords: Book review; Integrated Development Planning; Skills and resources; Future, change and choice